Answer:
2(n - 10)(3n + 2)
Explanation:
Given
6n² - 56n - 40 ← factor out 2 from each term
= 2(3n² - 28n - 20) ← factor the quadratic
Consider the factors of the product of the n² term and the constant term which sum to give the coefficient of the n- term.
product = 3 × - 20 = - 60 and sum = - 28
The factors are - 30 and + 2
Use these factors to split the n- term
3n² - 30n + 2n - 20 ( factor the first/second and third/fourth terms )
= 3n(n - 10) + 2(n - 10) ← factor out (n - 10) from each term
= (n - 10)(3n + 2)
Thus
6n² - 56n - 40 = 2(n - 10)(3n + 2)